Pemberdayaan Perempuan Untuk Berkarir dan Berbisnis Melalui Platform Digital Instagram @wewaw.id - Hidayati Purnama; Joko Santoso; Agung Kurniawan (Universitas Lambung Mangkurat, 2025)
Instagram is an effective digital platform for women's empowerment. Instagram has features to turn personal accounts into professionals, one of which is the community. The presence of digital communities certainly supports women's empowerment, including WEWAW (Women Empower Women at Work) with a commitment to provide references, education, and assistance for Indonesian women in their careers and businesses. This research aims to analyse how the content and programs on Instagram @wewaw.id represent efforts to empower women to have a career and do business. This research uses qualitative methods with content analysis techniques, collects data through Instagram accounts and literature studies from documents and books, and uses data triangulation by utilising several different sources of information. The results showed that the wewaw community successfully empowered women through seven stages of empowerment: awareness, freedom, capacity building, empowerment, achievement of results, evaluation, and a follow-up stage. The community uses symbols such as feminine colours, cartoon illustrations of women, and keywords such as